Incremental Nonlinear Dynamic Inversion Considering Centroid Variation Control for Reusable Launch Vehicles - Qiushi Tang; Jiahao Gan; Yuanpeng Fang (Aerospace, 2025)
For the diverse payloads of Reusable Launch Vehicles and the inevitable problem of change in the center of mass, this paper proposes an incremental nonlinear dynamic inversion considering centroid variation control. Regarding the trans-atmosphere flight environment, the six-degree-of-freedom dynamics model considering centroid shift, Earth rotation, and the Clairaut Ellipsoid Model is established to improve model accuracy. An incremental nonlinear dynamic inversion considering a centroid variation controller with excellent dynamic performance and adjustment under the centroid variation is designed for the model, which fully meets the safety requirements of RLV reentry. An extended state observer considering centroid variation is proposed to solve the problem with difficult direct measurement of angular acceleration, which incorporates the influence of centroid variation into the known part to improve estimation accuracy and speed. Finally, the simulation results are provided to verify the robustness of the change of centroid position and good control quality with the proposed controller.